Innovative Textile Desiging for Ladies Apparels from Architectural Motifs of Sethi House - Saba, Saraj ul; Rafique, Shabana; Tauqeer, Faiza; Seemi, Imrana (Pakistan Journal of Humanities and Social Sciences, 2023)
This study describes the uniqueness of traditional architectural motifs of the Sethi house situated in city of Khyber Pukhtun Khawa, Pakistan with respect to the revival of these motifs by digital printing on ladies apparel. Textile designs from historical motifs have initiated to be used frequently in various textiles industries. Goods designed in today’s fashion world play a significant role in the conservation of historical and cultural ideas. The combination of contemporary styles with timeworn designs and motifs safeguards the existence of these motifs for looming products. The Sethi house comprise of superb architectural elements like engraved woodwork, ainah kari, and jaili work etc. Sethi house interior is planned with so simple, yet complex pure Islamic architecture motifs that one could look at these features for hours.Designs from the ceiling of the rooms comprising unique jaliwork, naqqashi and courtyard decorating elements were selected for transformation in to textile designs through Adobe photo shop software. Various types of fabric specimens were digitally printed, stitched in to female costumes and exhibited for the students and numerous personnel belonging to fashion designing field. The data was collected through questionnaires by ranking the textile designs subjectively and statistically analysed regarding transformation of motifs, form, novelty, symbolism, aesthetics, texture, different color schemes, and commercial acceptability in the market. This work will help those designers who are striving to recover their own traditional details with the modern-day fashion movements. Architectural motifs of Sethi House can be a source of inspiration for current fashion designers to boost their culture in domestic as well as global market.